Association of Ancillary Pathology Findings in Non-neoplastic Renal Parenchyma and Renal Outcomes of Robotic-Assisted Partial Nephrectomy - Geldmaker, Laura E.; Kahn, Amanda E.; Parikh, Kevin A.; Porter, Ivan E.; Haehn, Daniela A.; Bajalia, Essa M.; Zhai, Qihui; Ball, Colleen T.; Thiel, David D. (Frontiers in Surgery, 2021)
Background: To evaluate robotic-assisted partial nephrectomy (RAPN) renal outcomes associated with ancillary pathology findings in non-neoplastic renal parenchymal tissue. Methods: Tissue samples from 378 RAPNs were analyzed for glomerular disease (GD), vascular disease (VD), and tubulointerstitial disease (TD). 152 patients were excluded due to insufficient non-neoplastic tissue for analysis and 4 patients were excluded due to calyceal diverticulum. Non-neoplastic tissue was evaluated for GD (negative, moderate, or global), VD (absent, mild, moderate, or severe), and TD (present or absent). Associations of ancillary pathology factors with patient characteristics were explored using the non-parametric Kendall tau test and propensity score adjusted longitudinal mixed effects regression models were used to evaluate associations of these pathology factors with changes in eGFR following RAPN. Results: 153 (68.9%) patients had hypertension and 50 (22.5%) patients had diabetes. Majority of patients did not have any GD (N=158, 71.2%) or TD (N=186, 83.8%) while 129 (58.1%) had VD. VD was categorized as absent (N=93, 41.9%), mild (N=45, 20.3%), moderate (N=76, 34.2%), and severe (N=8, 6.8%). Older age (P=0.018), hypertension (P<0.001), and high grade MAP score (P=0.047) were associated with a higher number of ancillary pathology factors. High grade MAP score (P=0.03, P=0.002) and hypertension (P=0.02, P<0.001) were individually associated with GD severity and VD severity, respectively. Older age was also individually associated with VD severity (P=0.002) and hypertension was associated with TD (P=0.04). Moderate-to-severe VD was associated with a worse change in eGFR from pre-RAPN to 1-month post-RAPN compared to those with mild or no VD (difference in mean change, -3.4 ml/kg/1.73m2; 95% CI, -6.6 to -0.2 ml/kg/1.73m2; P=0.036). Conclusions: Moderate-to-severe VD in non-neoplastic renal parenchyma is associated with postoperative changes in eGFR. Older age, hypertension, and high grade MAP scores are associated with the number of ancillary pathologies observed in RAPN specimens.